Design of Nanosuspensions and Freeze‐Dried PLGA Nanoparticles as a Novel Approach for Ophthalmic Delivery of Pranoprofen. Issue 10 (4th August 2014) - Abrego, Guadalupe; Alvarado, Helen L.; Egea, Maria A.; Gonzalez‐Mira, Elizabeth; Calpena, Ana C.; Garcia, Maria L.
<x xml:space="preserve">Abstract</x> Pranoprofen (PF)‐loaded poly (lactic‐co‐glycolic) acid (PLGA) nanoparticles (NPs) were optimized and characterized as a means of exploring novel formulations to improve the biopharmaceutical profile of this drug. These systems were prepared using the solvent displacement technique, with polyvinyl alcohol (PVA) as a stabilizer. A factorial design was applied to study the influence of several factors (the pH of the aqueous phase and the stabilizer, polymer and drug concentrations) on the physicochemical properties of the NPs. After optimization, the study was performed at two different aqueous phase pH values (4.50 and 5.50), two concentrations of PF (1.00 and 1.50 mg/mL), three of PVA (5, 10, and 25 mg/mL), and two of PLGA (9.00 and 9.50 mg/mL). These conditions produced NPs of a size appropriate particle size for ocular administration (around 350 nm) and high entrapment efficiency (80%). To improve their stability, the optimized NPs were lyophilized. X‐ray, FTIR, and differential scanning calorimetry analysis confirmed the drug was dispersed inside the particles. The release profiles of PF from the primary nanosuspensions and rehydrated freeze‐dried NPs were similar and exhibited a sustained drug delivery pattern. The ocular tolerance was assessed by an HET‐CAM test. No signs of ocular irritancy were detected (score 0). © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:3153–3164, 2014